1997
DOI: 10.1021/ja963258r
|View full text |Cite
|
Sign up to set email alerts
|

Hexacoordination via Sulfur Donor Action in Nitrogen and Chlorine Bonded Bicyclic Tetraoxyphosphoranes1

Abstract: Oxidative addition reactions of a quinone with the sulfur containing cyclic chlorophosphine S[(t-Bu)MeC6H2O]2PCl (1) yielded the new bicyclic tetraoxyphosphoranes, S[(t-Bu)MeC6H2O]2PCl(O2C6Cl4) (2) and S[(t-Bu)MeC6H2O]2PCl(O2C14H8) (5). Further new derivatives of this class were prepared by chlorine displacement reactions of 2 and 5 to give S[(t-Bu)MeC6H2O]2P(NHC6H4Me)(O2C6Cl4) (3), S[(t-Bu)MeC6H2O]2P(NMe2)(O2C6Cl4) (4), S[(t-Bu)MeC6H2O]2P(NHCH2C6H5)(O2C14H8) (6), and S[(t-Bu)MeC6H2O]2P(NMe2)(O2C14H8) (7). X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 25 publications
1
52
0
Order By: Relevance
“…The electronegativity effect is clearly evident on going from pentaoxyphosphoranes to tetraoxyphosphoranes, where ligands of lower electronegativity replace attached oxygen atoms. This is seen in the tetraoxyphosphorane 16, 35 which has an NMe 2 group in place of a pentafluorophenyl group in the pentaoxyphosphorane 17. 48 This results in over a 0.2 Å shortening in the P-S distance in 17 relative to 16.…”
Section: Hexacoordinate Phosphorusmentioning
confidence: 99%
“…The electronegativity effect is clearly evident on going from pentaoxyphosphoranes to tetraoxyphosphoranes, where ligands of lower electronegativity replace attached oxygen atoms. This is seen in the tetraoxyphosphorane 16, 35 which has an NMe 2 group in place of a pentafluorophenyl group in the pentaoxyphosphorane 17. 48 This results in over a 0.2 Å shortening in the P-S distance in 17 relative to 16.…”
Section: Hexacoordinate Phosphorusmentioning
confidence: 99%
“…Previous studies have shown that phosphorus compounds undergo an increase in coordination geometry with sulfur, oxygen, , and nitrogen donor atoms that are present as part of flexible ring systems. As a consequence of donor interaction, oxyphosphoranes traverse a coordinate from square pyramidal to octahedral, , while phosphates, ,, phosphines, ,, and phosphites 2,13,14 are displaced toward trigonal bipyramidal (TBP).…”
Section: Introductionmentioning
confidence: 99%
“…The stability of the resulting P(VI) is emphasized by displacement coordinate experiment as shown in Scheme 11 [59]. If the sulfur atom is oxidized to a sulfonyl moiety, then oxygen donation occurs to the phosphorus as observed in compounds 49a-49h (Fig.…”
Section: Scheme 11mentioning
confidence: 99%
“…Since 1996, Holmes and coworkers have investigated further the formation of hexacoordinated phosphorus derivatives by virtue of sulfur donation [59][60][61][62][63][64].…”
Section: Via P-s or P-o-s Interactionsmentioning
confidence: 99%